Catalytic asymmetric propargyl- and allylboration of hydrazonoesters: a metal-free approach to sterically encumbered chiral α-amino acid derivatives. Issue 91 (30th October 2018) - Jonker, Sybrand J. T.; Diner, Colin; Schulz, Göran; Iwamoto, Hiroaki; Eriksson, Lars; Szabó, Kálmán J.
Abstract : Metal-free asymmetric catalysis for the synthesis of sterically encumbered amino-acids was developed using allyl- and allenylboronic acid reagents. Abstract : A new asymmetric catalytic propargyl- and allylboration of hydrazonoesters is reported. The reactions utilize allenyl- and allylboronic acids in the presence of the inexpensive parent BINOL catalyst. The reactions can be performed under mild conditions (0 °C) without any metal catalyst or other additives affording sterically encumbered chiral α-amino acids. This is the first metal-free method for the asymmetric propargyl- and allylboration of hydrazonoesters.